Overview of Rheumatoid Arthritis therapy: Management options in Indonesia - Fia Fia; Johanna Westra (Fakultas Kedokteran Universitas Tarumanagara, 2018)
Rheumatoid arthritis (RA) is chronic disease characterized by inflammation of the synovium, affecting small joints and many other tissues. RA patients experienced loss of functionality, reduced quality of life, and increased morbidity and mortality. The prompt treatment is very important to alleviate sign and symptoms, reduce disability, increase quality of life and halt the progression of joint damage. Pathogenesis of rheumatoid arthritis involves complex interaction of host immunity, environmental factors and genetic predisposition. Treatment strategy for RA has changed over the past 20 years. Traditional approach as administration of non-steroidal anti-inflammatory drugs (NSAIDs) for acute disease had been abandoned. Current strategy includes administration of disease-modifying antirheumatic drugs (DMARDs) as first line therapy. “Treat to target” approach in RA management is directed to achieve clinical remission or at least low-disease activity for RA patients. Unfortunately, many factors are limiting DMARDs therapy for RA patients in Indonesia. Methotrexate should be first line treatment for patients with RA who have access to this agent. Patients who can afford biologic DMARDs could benefit from these agents. However, biologic agents are reported to increased risk of infections, including opportunistic infections. For an endemic country as Indonesia, administration of biologic agents requires a careful observations and screening. In Indonesia, conventional DMARDs as chloroquine and glucocorticoids are the most accessible and cheapest for patients and primary health provider as general practitioners. Hence, for patients that do not have access to rheumatologists and internists, these drugs could be an option.